Biological Efficacy of Plant Growth–Promoting Bacteria and Arbuscular Mycorrhizae Fungi: Assessments in Laboratory and Greenhouse Conditions. Issue 4 (20th April 2023) - Gelvez‐Pardo, Ivonn; Lobo‐Berbesi, Laura; Santos‐Díaz, Adriana
Abstract: Utilizing the interactions of microorganisms with plants offers a favorable path to increase crop production and replace the use of synthetic fertilizers. Different bacteria and fungi have been used as biofertilizers to improve agricultural production, yield, and sustainability. Beneficial microorganisms can act as free‐living organisms, symbiotes, and endophytes. Soil bacteria called plant growth–promoting bacteria (PGPB) and fungi called arbuscular mycorrhizae fungi (AMF) stimulate the growth and health of plants by direct and indirect mechanisms including nitrogen fixation, phosphorus solubilization, phytohormone production, enzyme production, antibiotic synthesis, and induced systemic resistance. To use these microorganisms as a biofertilizer, it is necessary to assess their efficacy under laboratory and greenhouse conditions. Few reports detail the methods used to develop a test under different environmental conditions, and without these details it is difficult to develop suitable methodologies to evaluate microorganism‐plant relationships. We describe four protocols that go from sample preparation to testing in vitro the efficacy of different biofertilizers. Each protocol can be used to test a different biofertilizer microorganism, focusing on bacteria such as Rhizobium sp., Azotobacter sp ., Azospirillum sp., Bacillus sp. as well as AMF such as Glomus sp. These protocols can be used in several stages of biofertilizer development, including microorganism selection, microorganism characterization, and in vitro evaluation of efficacy for the registration process. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Evaluating the biological effect of biofertilizer based on PGPB under laboratory conditions Basic Protocol 2 : Evaluating the biological effect of biofertilizer based on PGPB under greenhouse conditions Basic Protocol 3 : Evaluating the biological effect of biofertilizer based on symbiotic nitrogen‐fixing bacteria Basic Protocol 4 : Evaluating the biological effect of biofertilizer based on AMF